Investigation of the Characteristics of the Obtained Extraction Phosphoric Acid and Phosphogypsum from Unfired Phosphorites - Khurramov Navruzbek, Nurmurodov Tulkin, Erkaev Aktam, Kucharov Bakhrom (International Journal of Modern Agriculture, 2021)
In this article, the process of obtaining wet-process phosphoric acid (WPPA) from unburnt washed, dried phosphorite concentrates of Central Kyzylkum (UWDC PCK) is studied. The influence of the duration of the extraction process and the ratio of fat was studied: T for the output technological parameters of the process. It was found that the decomposition of UWDC PCK in the presence of a circulating solution of 16.2% P2O5 showed that the decomposition process takes place completely, at 80-85 oC in 2 hours, quite easily and quickly without excess sulfuric acid. At the same time, there is no intensive foaming, which is characteristic of unfired phosphorite of the Central Kyzylkum.